REMEDIAL MEASURES FOR IMMOBOLIZATION OF HEAVY METALS FROM CONTAMINATED SOIL - Sharma, Baby; Chettri, Mukesh Kumar (Ecoprint: An International Journal of Ecology, 2014)
To understand the remedial measures of heavy metals from contaminated soil, three vegetable (Brassica juncea, Brassica rapa and Lepidium sativum) were grown on soil artificially contaminated with 300 mg kg-1 CuCl2, 500 mg kg-1 Pb(NO3)2, 800 mg kg-1 ZnCl2 or their mixed metal (1600 mg kg-1). This experiment showed that Cu and Pb accumulation in vegetables are higher in lime treatments than in 20% cowdung treatments. Zinc accumulation increased in B. rapa and L. sativum in both cow dung and lime treatments compared to control. Accumulation of Cu, Pb and Zn from mixed metal treatment was highest in L. sativum (at lime 9 g kg-1 for Cu and Pb, and 20% cow dung for Zn). Morphological changes such as fresh weight, dry weight, shoot length, root length, mostly increased significantly (P≤0.01) with Zn and cow dung treatment, but none with lime treatment. Fresh and dry weight increased only in L. sativum grown in 3 g kg-1 lime treatment. Immobilization of Cu, Pb and Zn in both single and mixed treatments was found to be high in cow dung amended soil. From this it can be ascertained that 20% cow dung treatment is suitable for immobilization of supplied heavy metals than lime treatments. DOI: http://dx.doi.org/10.3126/eco.v19i0.9853 Ecoprint An International Journal of Ecology Vol. 19, 2012 Page: 1-5 Uploaded date: 2/14/2014